THE EFFECT OF BUSINESS RISK, LIQUIDITY, SOLVENCY AND CASH CONVERSION CYCLE ON PROFITABILITY - Partogian Sormin; Shelly Yolanda (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
The core objective of this research is to determine the effect of business risk, liquidity, solvency and cash conversion cycle on the profitability of companies in the consumer goods industry. The study variables measured were: business risk, liquidity, solvency and cash conversion cycle. The source of the data collected from this study is secondary data which is in the form of financial statements of companies listed on the IDX for the 2014-2020 period. The research sampling method used purposive sampling which was processed using the SPSS version. The results of the study found that business risk, liquidity, solvency and cash conversion cycle have a simultaneous effect on company profitability. The results of the hypothesis test found that business risk has no positive effect on profitability, liquidity has no positive effect on profitability, solvency has a positive effect on profitability and the cash conversion cycle has a positive effect on profitability. Thus this study is able to provide positive and relevant information for stakeholders in predicting profitability through independent variables as predictors.